Analysis on the Moderating Effect of Innovation and Entrepreneurship Education Mode and Locus of Control of College Teachers and Students Based on Comic Style Recognition - Li, Bingjie; Ren, Kangshun; Guo, Qiyang; Huang, Xiaohong; Chen, Jianjun (Frontiers in Psychology, 2022)
This study was carried out to explore the moderating effect of comic education and locus of control (LOC) in innovation and entrepreneurship education in colleges and universities. Firstly, the theoretical knowledge of comic education, innovation and entrepreneurship education, and LOC was briefly introduced, and the significance of comics for innovation and entrepreneurship education was discussed. Secondly, the existing innovation and entrepreneurship education modes in colleges and universities in China were introduced. Thirdly, a simple comparative analysis was conducted on the internal and external characteristics of LOC. Finally, an investigation was performed on the innovation and entrepreneurship ability of college students. The results demonstrate that the average score of students’ innovation spirit is 3.302, with a standard deviation of 0.481, suggesting that the current college students’ overall innovative spirit is moderate. Besides, students get moderate scores in each dimension, and the difference between different students is slight. Among them, the mean of reflectiveness is the highest (M=3.446, SD=0.540), and the mean of criticality is the lowest (M=3.160, SD =0.481). The average score of the current students’ entrepreneurial ability is 3.112, indicating that the students’ entrepreneurial ability is above the average. From the perspective of each dimension, students have the lowest score in opportunity discovery ability, which is at a low level (M=2.821, SD=0.873), while the other five dimensions are at a medium level. The highest is strategic decision-making ability (M=3.264, SD=0.749). At the same time, factors such as gender, grade, institution, and students’ relatives significantly impact students’ innovation and entrepreneurship ability. It can be concluded that colleges and universities should focus on controlling the quality of innovation and entrepreneurship teaching and guiding and carrying out innovation and entrepreneurship practice activities. They should also encourage students to participate in courses and activities related to innovation and entrepreneurship to improve college students’ innovation and entrepreneurship ability.